Comparative Studies on Al-Based Composite Powder Reinforced with Nano Garnet and Multi-wall Carbon Nanotubes - Basariya M.R.; Srivastava V.C.; Mukhopadhyay N.K. (My University, 2025)
Effect of mechanical alloying/milling on microstructural evolution and hardness variations of garnet and multi-walled carbon nanotubes (MWCNTs)-reinforced Al-Mg-Si alloy (EN AW6082) composites are investigated. Structural and morphological studies revealed that the composite powders prepared by milling display a more homogenous distribution of the reinforcing particles. Improved nanoindentation hardness viz., 4.24 and 5.90 GPa are achieved for EN AW6082/Garnet and EN AW6082/MWCNTs composites, respectively, and it is attributed to severe deformation of the aluminum alloy powders and embedding of the harder reinforcement particles uniformly into the aluminum alloy matrix. However, enhancement in case of MWCNTs-reinforced composite makes apparent the effect of its nanosized uniform dispersion in the matrix, thereby resisting the plastic deformation at lower stress and increased dislocation density evolved during high-energy ball milling. The results of the present study indicate that carbon nanotubes and garnet can be effectively used as reinforcements for Al-based composites. © 2015, ASM International.